Analysis of mode i conducting crack in piezo-electro-magneto-elastic layer - Rogowski, Bogdan (Zielona Góra: Uniwersytet Zielonogórski)
Within the theory of linear magnetoelectroelasticity, the fracture analysis of a magneto - electrically dielectric crack embedded in a magnetoelectroelastic layer is investigated. The prescribed displacement, electric potential and magnetic potential boundary conditions on the layer surfaces are adopted. Applying the Hankel transform technique, the boundary - value problem is reduced to solving three coupling Fredholm integral equations of second kind.
Keywords: magneto electro elastic layer; Penny - shaped crack; dielectric crack; field intensity factors; exact solution